Reproductive Strategy of Labeobarbus batesii (Boulenger, 1903) (Teleostei: Cyprinidae) in the Mbô Floodplain Rivers of Cameroon - Tiogué, Claudine Tekounegning; Tomedi, Minette Tabi Eyango; Tchoumboué, Joseph (International Journal of Zoology, 2013)
Aspects of the reproductive strategy of African carp, Labeobarbus batesii, were investigated from May 2008 to October 2009 in the Mbô Floodplain of Cameroon. Samples were collected monthly from artisanal fishermen. The total length and total body mass of each specimen were measured to the nearest mm and 0.01 g, respectively. Sex was determined by macroscopic examination of the gonads after dissection. The sex ratio was female skewed (overall sex ratio: 1 : 1.42). Females reach sexual maturity at a larger size (213 mm) than the males (203 mm). The mean gonadosomatic index ranges from 0.32±0.17% to 1.91±1.15%, whereas the mean K factor ranges from 0.90±1.09 to 1.10±0.13. These two parameters are negatively correlated. The reproduction cycle begins in mid-September and ends in July of the next year, and they are reproductively quiescent for the rest of the year. Labeobarbus batesii is a group-synchronous spawner with pulses of synchronised reproduction spread over a long period. The mean absolute, potential, and relative fecundities are 2898±2837 oocytes, 1016±963 oocytes, and 9071±7184 oocytes/kg, respectively. The fecundity is higher and positively correlated with the gonad mass than with body size. Its reproductive biology suggests that L. batesii is suitable for pond culture.